Local knowledge production, transmission, and the importance of village leaders in a network of Tibetan pastoralists coping with environmental change - Hopping, Kelly A., author; Yangzong, Ciren, author; Klein, Julia A., author; Resilience Alliance, publisher (Colorado State University. Libraries, 2016)
Changing climate, social institutions, and natural resource management policies are reshaping the dynamics of social-ecological systems globally, with subsistence-based communities likely to be among the most vulnerable to the impacts of global change. These communities’ local ecological knowledge is increasingly recognized as a source of adaptive capacity for them as well as a crucial source of information to be incorporated into scientific understanding and policy making. We interviewed Tibetan pastoralists about their observations of environmental changes, their interpretations of the causes of these changes, and the ways in which they acquire and transmit this knowledge. We found that community members tended to agree that changing climate is driving undesirable trends in grassland and livestock health, and some also viewed changing management practices as compounding the impacts of climate change. However, those nominated by their peers as experts on traditional, pastoral knowledge observed fewer changes than did a more heterogeneous group of people who reported more ways in which the environment is changing. Herders mostly discussed these changes among themselves and particularly with village leaders, yet people who discussed environmental changes together did not necessarily hold the same knowledge of them. These results indicate that members of the community are transferring knowledge of environmental change primarily as a means for seeking adaptive solutions to it, rather than for learning from others, and that local leaders can serve as critical brokers of knowledge transfer within and beyond their communities. This highlights not only the interconnectedness of knowledge, practice, and power, but also points toward the important role that local governance can have in helping communities cope with the impacts of global change.
Keywords: cultural consensus analysis; global change; local ecological knowledge; pastoralism; social networks; Tibetan Plateau